Tema Arsitektur Tropis Kontemporer pada Rancangan Bangunan Pusat Komunitas dan Pelatihan Urban Farming di Surabaya Timur - Devani Pramisdiantari; Failasuf Herman Hendra; Siti Azizah (Institut Teknologi Adhi Tama Surabaya, 2022)
The whole world is currently facing the Covid-19 pandemic, survival efforts have been made to avoid being exposed to the Corona Virus. Indonesia is also facing a crisis when implementing a long-lasting lockdown. Now residents in the city are starting to do various activities at home and the popular one is farming. In Surabaya, urban farming enthusiasts increased during the pandemic, the high demand for plant seeds during the PSBB period caused the relevant agencies to experience limited stock of plant seeds. In order to support the development of urban farming and the provision of various plants, the idea of designing a community container building and an adequate training place for farming is very much needed. The research for this design uses a descriptive method, namely a case study research method that provides explanations using descriptive analysis. This building will function as an educational and entertainment facility located on JL. Raya Medokan Sawah, Surabaya. The space program consists of several facilities, including main facilities, supporting facilities, service facilities, management facilities. The theme raised is contemporary tropical architecture, which combines the themes of tropical and contemporary architecture. This is intended to create a representative form, land structure, and building space for farming based on awareness of climate change, but with an expressive and simple display of contemporary architectural styles to create a harmonious reciprocal relationship between humans and nature.